2020
DOI: 10.3389/fmed.2020.544697
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Community-Based Osteoporosis and Associated Fractures in Beijing: Study Protocol for a Cross-Sectional and Prospective Study

Abstract: Background: Osteoporosis (OP) patients are usually asymptomatic until osteoporotic fractures occur, which makes early diagnosis and prevention difficult, and the associated fractures secondary to OP could be preventable with appropriate management. Therefore, early identification and relevant evidence-based management of OP could guide the prevention of subsequent fractures. This study will investigate the prevalence of OP and the incidence of osteoporotic fractures in Beijing community residents to further ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Clinical and experimental studies demonstrated MP as a common cause of osteoporosis through stimulation of osteoclastogenesis, bone resorption, apoptosis of mature osteoblasts, and osteocytes, resulting in bone loss and fragility (Canalis, 2005; Sun et al, 2020). At the molecular level, MP increases the expression of RANKL, as a membrane‐bound molecule of the tumor necrosis factor ligand family, which is expressed in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical and experimental studies demonstrated MP as a common cause of osteoporosis through stimulation of osteoclastogenesis, bone resorption, apoptosis of mature osteoblasts, and osteocytes, resulting in bone loss and fragility (Canalis, 2005; Sun et al, 2020). At the molecular level, MP increases the expression of RANKL, as a membrane‐bound molecule of the tumor necrosis factor ligand family, which is expressed in osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that prednisolone administration could damage the structure of the tibia represented by the occurrence of the increasing lacunae, thinning trabeculae, resulting in bone fragility (Canalis, 2005; Sun et al, 2020). The result of this study revealed that MP administration caused a significant decline in bone stiffness which was significantly improved by PSL‐Cur administration which was evaluated using a biomechanical three‐point bending test on the rats' tibia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this community-based cross-sectional and prospective follow-up study, 24 we sought 1055 postmenopausal women who responded to an invitation to participate from Chaoyang District or Fengtai District in Beijing. Then, the participants were screened, based on predetermined inclusion and exclusion criteria.…”
Section: Methodsmentioning
confidence: 99%